Vignette for enhancing Pluridisciplinary course development: 2020 a framework for course development. - West, Jason M.; Kinash, Shelley; Bannatyne, Amy (Australia. Dept of Education, Skills and Employment, 2020)
The theme of this vignette is pluridisciplinary course development using a framework. The objective validation of pluridisciplinary programs is the second vignette in this series. The project took place between November 2015 and March 2017. The study was designed to consult, share, and create awareness of alternative learning and teaching practices for pluridisciplinary fields. Pluridisciplinarity, coined by Max-Neef (2005), requires two or more disciplines to combine their expertise to jointly develop and deliver learning and teaching outcomes appropriate for a subject area, especially one that is rapidly changing. Emerging careers in technology-focused fields coupled with necessary graduate outcomes mandate the need for a truly pluridisciplinary pedagogical approach. Pluridisciplinary collaboration occurs when people from different professions or disciplines with varied skills and experiences complement each other when working toward achieving a common objective. [Publisher summary, ed]